SemiÃ³tica del consumo. MetodologÃa para el anÃ¡lisis publicitario desde una perspectiva integral - Eduardo YalÃ¡n Dongo (Ocula)
The aim of this article is to propose a consistent methodological approach for the analysis of advertising discourse and consumption practices from a perspective that integrates market economy semiotically as context. It argues that there is an epistemological limitation in semiotic analysis of consumption due to methodological commitments during the analysis procedure. Thus, advertising and consumption semiotics, limited to the analysis of a single text (commercial, billboard, advertisement), assume their object of study as abstracted from social relations. From this âmonotextualâ viewpoint, the consumer society is conceived as a contextual production framework that does not participate in the semiotic interpretation of advertising materials. This article advocates for a semiotics capable of integrating advertising discourses, consumption practices, and various historical processes of the market economy by considering them as texts. To achieve this, it presents the methodological approach assuming an expanded notion of textuality, affirming the market economy as part of the production of meaning in advertising materials. Once the context (economy) is established as another text, three main logics (practical-critical/manufacture, utopian/semiocapitalism, and ludic/hyperconsumption) are identified between advertising discourse and consumption practices. This methodological model stands as an analytical tool for the analysis of advertising discourse.